Ogichitaakwe regeneration - McGuire Adams, Tricia (2009)
This thesis explores regenerating Anishinaabekwe (women’s) empowerment. The teaching of the ogichitaakwe (an Anishinaabekwe who is committed to helping the Anishinaabe people) was investigated to gain knowledge of how this aspect of the Anishinaabekwe ideology can be used to challenge the effects of colonialism in community. The goal of the thesis is to frame solutions to the effects of colonialism from the foundation of empowerment via the Anishinaabekwe ideology. The thesis examines how the Anishinaabekwe ideology in collaboration with radical indigenous feminism is useful in challenging colonialism. To this end, the utilization of self-consciousness-raising groups or Wiisokotaatiwin (gathering together for a purpose) provides the opportunity to address personal decolonization and regeneration. The author will show that by committing to the Anishinaabekwe ideology, the effects of colonialism will be addressed from a place of empowerment and ultimately regenerate the Anishinaabe Nation.